Characterization of the Estrogen Response Helps to Predict Prognosis and Identify Potential Therapeutic Targets in Cholangiocarcinoma - Lu, Chenglin; Miao, Ji; Li, Minhuan; Zheng, Qisi; Xu, Feng; Pan, Yiming; Wang, Yizhou; Yang, Zhi; Xia, Xuefeng; Zhu, Hao; Chen, Jie; Bao, Shanhua (Frontiers in Oncology, 2022)
Cholangiocarcinoma (CCA) is an aggressive malignancy originating from the epithelium of the bile duct. The prognosis of patients is poor regardless of radical resection and chemoradiotherapy. The current classification and prognostic model of CCA are unable to satisfy the requirements for predicting the clinical outcome and exploring therapeutic targets. Estrogen signaling is involved in diverse cancer types, and it has long been established that CCA could be regulated by estrogen. In our study, estrogen response was identified to be significantly and stably correlated with poor prognosis in CCA. Employing several algorithms, CCA was classified into ES cluster A and B. ES cluster B was mainly composed of patients with fluke infection and overlapped with CCA cluster 1/2, and ES cluster A was mainly composed of patients without fluke infection and overlapped with CCA cluster 3/4. COMT and HSD17B1 were identified to be responsible for the differential estrogen response between ES clusters A and B, and the estrogen response may be correlated with the differentiation and cancer stemness of CCA at the single-cell level. Complement activation and the expression of C3 and C5, which are mainly expressed by CCA cells, were significantly downregulated in ES cluster B. An estrogen response risk score (ESRS) model was constructed to predict the prognosis of CCA, followed by a nomogram integrating ESRS and clinical features. Finally, altered pathways, applicable drugs and sensitivity to chemical drugs were analyzed specific to the estrogen response. In summary, our results provide insights into the role of the estrogen response in CCA progression as well as applicable drugs and potential therapeutic targets in estrogen metabolism, the complement system and ESRS-related pathways.